Review of “Doing Poetic Inquiry” by Helen Owton (2017) - MacKenzie-Dawson, Sarah K. (Art/Research International, 2022)
Directed toward the novice, Helen Owton’s (2017) book, Doing Poetic Inquiry, introduces the reader to poetry as an approach to research that allows one to enter into a phenomenological space of relational experience and understanding. Striving toward accessibility, she captures the tensions that exists within qualitative research by offering a guide that is both personal and methodologically orientated. Across the space of this review, I blend found poetry with prose as a means of entering into dialogue with this work. This dialogue lives in a messy space of intention and understanding where knowing lives within the body—the heart, the personal and political. Owton’s work is a compassionate gesture that offers concrete examples and suggestions inviting the reader to reconsider their own research practices and the discursive spaces in which those practices live.